2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009240
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface electromyography patterns of healthy and incomplete spinal cord injury subjects interacting with an upper-extremity exoskeleton

Abstract: Abstract-Rehabilitation exoskeletons may make use of myoelectric control to restore in patients with significant motor impairment following a spinal cord injury (SCI) a sense of volitional control over their limb -a crucial component for recovery of movement. Little investigation has been done into the feasibility of using surface electromyography (sEMG) as an exoskeleton control interface for SCI patients, whose impairment manifests in a highly variable way across the patient population. We have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Reference [164] has used FSR sensors for the payload estimation of robotic exoskeleton. Moreover, force sensors including FSRs and load cells are being used to measure the interaction pressure over the whole contact area between the upper limb and exoskeleton [48,50,55,79,165,166]. Besides, several studies have proposed neural/muscular sensing and shown its significance for exoskeleton control.…”
Section: Sensing and Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference [164] has used FSR sensors for the payload estimation of robotic exoskeleton. Moreover, force sensors including FSRs and load cells are being used to measure the interaction pressure over the whole contact area between the upper limb and exoskeleton [48,50,55,79,165,166]. Besides, several studies have proposed neural/muscular sensing and shown its significance for exoskeleton control.…”
Section: Sensing and Estimationmentioning
confidence: 99%
“…The complex relative movements between the radial and ulna bones make it difficult to develop a mechanism which can precisely replicate the forearm supination/pronation. Few studies [6,22,33,34,50,58,70,72,167] have presented a design that can actively support the users in executing forearm supination/pronation by taking into account the effect of radial/ulnar deviation.…”
Section: Ergonomic and Standardized Designmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure passivity, two bipolar surface electromyography (sEMG) electrodes were used. Each sEMG electrode was located on the user's forearm to measure muscle activity related to wrist flexion and extension, using electrode placements similar to [23] (see Fig. 8).…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of this method for daily routine activities or factory tasks is not feasible, where the user carries objects of different attributes. To overcome this challenge, Electromyography (EMG) based estimation methods are used instead to determine joint torques and provide assistance through exoskeletons McDonald et al (2017); Mangukiya et al (2017); Leonardis et al (2015); Abdallah et al (2017); Mghames et al (2017); Tang et al (2014); Rahman et al (2015); Li et al (2013); Kiguchi and Hayashi (2012). In these methods the assistance to each joint is provided by analyzing the muscle activities of its prime mover muscle group.…”
Section: Introductionmentioning
confidence: 99%